Macronyssus crosbyi - Orlova, M. V.; Klimov, P. B.; Orlov, O. L.; Smirnov, D. G.; Zhigalin, A. V.; Budaeva, I. V.; Emelyanova, A. A.; Anisimov, N. V. (Zenodo, 2021)
Macronyssus crosbyi (Ewing & Stover, 1915) Liponyssus crosbyi Ewing & Stover, 1915: 109. Leiognathus crosbyi .— Ewing, 1923: 7. Ichoronyssus hasei Vitzthum, 1932: 23 (synonymy by Radovsky, 1966). Ichoronyssus kolenatii Fonseca, 1948: 280 (synonymy by Radovsky, 1966). Ichoronyssus crosbyi .— Fonseca, 1948: 299; Yunker & Radovsky, 1966: 98. Ichoronyssus britanicus .— Furman, 1950: 480 (misidentification). Ichoronyssus quadridentatus Strandtmann & Hunt, 1951: 462; Baker & Strandtmann, 1959: 225 (synonymy by Radovsky, 1966). Macronyssus crosbyi .— Radovsky, 1966: 94; 1967: 119; Anciaux de Faveaux, 1971: 52; Hoffmann et al ., 1972: 153; Whitaker, 1973: 1149; Yunker et al ., 1975: 252; Whitaker et al ., 1983; Whitaker & Maser, 1985: 73; Stanjukovich, 1990: 197; Ritzi et al ., 2001: tabl.; Reeves et al ., 2007: 53; Jaunbauere et al ., 2008: 40; Radovsky, 2010: 56. Type locality: Rockport, Missouri (Ewing & Stover, 1915). Type host: “ Vesper subulatus ” (Ewing & Stover, 1915). Material. M ex soprano pipistrelle Pipistrellus pygmaeus Leach, 1825 from biological station “Venevitinovo”, 4 June 2019, leg. O.L. Orlov, I. V. Budaeva. Distribution in Russian Federation: Karelia Republic (Lebedeva et al ., 2020), Voronezh Province (present paper), Krasnoyarsk Region (Orlova et al ., 2017a), Irkutsk Province (Orlova et al ., 2017a), Buryatiya Republic (Orlova et al ., 2017a), Yakutiya Republic (Orlova et al ., 2017a), Khabarovsk Region (Medvedev et al ., 1991), Magadan Province (Medvedev et al ., 1991), [Urals, Altai, Russian Far East— Orlova et al ., 2015d]. Distribution outside Russian Federation: Europe (Baltic states— Stanyukovich, 1990a; Jaunbauere et al ., 2008), North and South America (Radovsky, 1967; Hoffmann et al ., 1972; Presley 2004). Hosts (Old World): Eptesicus nilssonii (Stanyukovich, 1990a; Lebedeva et al ., 2020), Myotis daubentonii (Stanyukovich, 1990a), M . dasycneme (Stanyukovich, 1990a), M . mystacinus (Stanyukovich, 1990a), M . sibiricus (Orlova et al ., 2017a), M . brandtii ...